2016
DOI: 10.1016/j.jss.2015.06.048
|View full text |Cite
|
Sign up to set email alerts
|

Imaging surveillance and survival for surgically resected non–small-cell lung cancer

Abstract: Introduction The importance of imaging surveillance following treatment for lung cancer is not well characterized. We examined the association between initial guideline recommended imaging surveillance and survival among early stage resected NSCLC patients. Methods A retrospective study was conducted using SEER-Medicare data (1995–2010). Surgically resected patients, with Stage I and II NSCLC, were categorized by imaging received during the initial surveillance period (4–8 months) following surgery. Primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Unfortunately, there is no statistical analysis about the added value of a CT scan above chest radiography. A second outcome, on subgroup analysis, showed that patients with stage I NSCLC might have benefits from initial surveillance with CT scan in contrast to patients with stage II (17). Comparison with this study is not easy because our study focused on the whole period of follow-up until progression of disease instead of the initial surveillance and included both surgical and SBRT patients instead of only surgical patients.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Unfortunately, there is no statistical analysis about the added value of a CT scan above chest radiography. A second outcome, on subgroup analysis, showed that patients with stage I NSCLC might have benefits from initial surveillance with CT scan in contrast to patients with stage II (17). Comparison with this study is not easy because our study focused on the whole period of follow-up until progression of disease instead of the initial surveillance and included both surgical and SBRT patients instead of only surgical patients.…”
Section: Discussionmentioning
confidence: 93%
“…One study showed that the way of follow-up in the initial phase after surgery (4-8 months) resulted in a 5-year survival of 58% for a chest radiography versus 61% for a CT scan (17). An initial CT scan did not give a superior 5-year survival compared to no initial imaging (p=0.110).…”
Section: Discussionmentioning
confidence: 99%
“…Backhas et al analyzed the Surveillance, Epidemiology, and End Results (SEER)-Medicare linked database, evaluating imaging studies performed during a designated surveillance window of 4–8 months following surgical resection of lung cancer. They identified no difference in overall or lung cancer-specific survival in patients who underwent an imaging study during the specified window and those who did not [15]. A systematic review analyzing the survival benefit of CT following surgery for lung cancer identified 5 relevant papers, 3 of which identified a survival benefit to surveillance CT and 2 of which did not.…”
Section: Discussionmentioning
confidence: 99%
“…[12,13] A meta-analysis suggested a slight mortality benefit to surveillance, but cautioned against drawing definitive conclusions given the wide range of study designs. [63] In a recent analysis of surgically treated early stage NSCLC patients, stage I patients who received early follow-up had significantly improved 5-year survival, [64] but whether ongoing surveillance over the entire recommended two-year post-treatment period was associated with improved survival was not assessed.…”
Section: Discussionmentioning
confidence: 99%